2021
DOI: 10.3390/app11041489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Edentulous Conditions on Intraoral Scanning Accuracy of Virtual Interocclusal Record in Quadrant Scan

Abstract: Reproduction of the exact interocclusal relationship using digital workflow is crucial for precise fabrication of accurate prostheses. Intraoral scanner is known to be valid for the measurement of quadrants, however, the role of missing area in the quadrant scan on the virtual interocclusal record (VIR) is uncertain. This study aimed to evaluate the accuracy of VIR in quadrant scans using an intraoral scanner (IOS) under four different edentulous conditions. Eight scans per group were obtained using a laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…On comparison of TRIOS, CS 3600, and i500, with a laboratory scanner, TRIOS had the best trueness (43.4 μm) followed by CS3600 (45.4 μm) and i500 (65 μm) 25 . A study carried out in dentate models has shown a significant difference between intraoral scanners.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…On comparison of TRIOS, CS 3600, and i500, with a laboratory scanner, TRIOS had the best trueness (43.4 μm) followed by CS3600 (45.4 μm) and i500 (65 μm) 25 . A study carried out in dentate models has shown a significant difference between intraoral scanners.…”
Section: Methodsmentioning
confidence: 94%
“…According to the study conducted by Lee, 25 a tilting effect was observed in the quadrant arch scan with the absence of posterior support or with more than two missing teeth. A possible explanation for this finding is the lack of landmarks in the edentulous area and the limitation of the scanner tip size, both of which could have contributed to the compromised estimation 25 . Depending on the scanner there can be overestimation or underestimation of the interocclusal distance hence, it might be necessary to compensate for the distortion of the occlusal relationship during the CAD or milling process 44 .…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…When a greater number or locations of teeth are being restored or when a patient has more than one missing tooth, complete-arch intraoral scans are recommended (Figures 2 and 3). [15][16][17][18][19]31,[63][64][65] It is important to remember that the accuracy of complete-arch intraoral scans for fabricating more than 4 restorations or FDPs involving more than 4 units, or complete-arch tooth-and implant-supported restorations by using IOSs is uncertain. [42][43][44][45][46][47]…”
Section: Complete-arch Scanmentioning
confidence: 99%
“…Due to the lack of anatomical landmarks and the presence of mobile tissue, edentulous spaces reduce the accuracy of the virtual definitive casts obtained by using IOSs 19,60–62 . Additionally, the accuracy of the maxillomandibular relationship at MIP captured by using IOSs can be also decreased when edentulous areas are present in a dental arch 19,63–65 . Studies have shown that the accuracy of recorded maxillomandibular relationship at MIP was significantly reduced in patients with edentulous spaces of two or more missing teeth 63,65 .…”
Section: Decision Criteria Factorsmentioning
confidence: 99%